Density of Tetraselmis sp. Cultured in Carboy Media with Different Nutrients - Chelsey Violeta Christya Archadia Cheres; Novia Salmatin; Lailatul Lutfiyah (Airlangga University, 2020)
Feed is the key to success in aquaculture, because it affects the resistance and development of larvae. There are two types of feed given to fish, namely artificial feed and natural feed. One type of natural feed that can be used as an enhancer for aquaculture feed needs is Tetraselmis sp.. So that practice is needed to learn, understand and practice directly the Tetraselmis sp. Natural feed culture techniques. laboratory scale. This research was held at the Brackish Water Aquaculture Center (BBPBAP) Jepara, Central Java for 46 days starting on December 17, 2018 until January 31, 2019. The culture technique consists of several stages including the preparation of tools and equipment, sterilization, fertilizer making, media preparation, calculation of inoculants, nutrition, seedling and maintenance. Based on observations for 16 days, Tetraselmis sp. has four growth phases consisting of adaptation, exponential, stationary and death phases. Tetraselmis sp. experienced the highest density on the tenth day with an average of 109.87 x 104 cells / ml. This shows that the growth of Tetraselmis sp. long enough than other species. After experiencing the exponential phase, Tetraselmis sp. experienced a stationary phase for 3 days and subsequently decreased density to reach 65.22 x 104 cells/ml on the sixteenth day. Keyword : Tetraselmis, Phytoplankton, Culture Technique